Activity of Political Parties in Uzbekistan: Formation and Development Prospects (Texas Journal of Multidisciplinary Studies, 2022)
This article analyzes the formation and types of political parties, party systems and the activities of political parties formed in Uzbekistan. The role of political parties in Uzbekistan in political processes and their influence on the formation of political culture of citizens were discussed.